Nutritional Status of SMA N 1 Bukit Sundi Students Solok District - Syahada, Rifa; Kasmita, Kasmita; Yuliana, Yuliana; Fridayati, Lucy (Jurnal Pendidikan Tata Boga dan Teknologi, 2024)
Adolescence is a transition period that is very vulnerable to nutritional problems. Likewise, young women occupy an important position in the flow of human life, because they will become prospective mothers who play a role in preserving and giving birth to quality generations and offspring in the future. The nutritional status of adolescent girls needs to be aforethought, where energy and protein intake, and knowledge about stabilized nutrition affect the nutritional status of adolescents. The attempt of this research was to determine the nutritional status of female students at SMA N 1 Bukit Sundi. The category of research is perceptive with a cross-sectional form. This research was carried out in April-May 2024, with a sample population of 100 people using a simple random sampling technique. Nutritional status was measured by the Body Mass Index (BMI) with data obtained through filling out questionnaires by research subjects, where research results showed that 40% of female students were included in the underweight nutritional category, 44% of female students were included in the underweight nutritional category. normal, 10% of female students fall into the overweight nutritional category, 5% of female students fall into the obese nutritional category level I, and 1% of female students fall into the obese nutritional category level II.